Urgensi Penguasaan Penerapan Variasi dalam Pembelajaran untuk Menumbuhkan Motivasi Belajar Siswa Sekolah Dasar - Juliantika Juliantika; Hana Nurur Rohmah; Syahla Rizkia Putri N; Siti Zahra Al Munawaroh (Departement of Mathematics Education, 2023)
This study discusses the importance of teachers mastering learning variation skills to foster elementary school students' learning motivation. The learning process is an activity that involves individuals directly. Learning activities are carried out on the basis of strong motivation from within the individual and outside the individual student. Therefore, the teacher's skill in mastering the application of learning variations is very important because it can generate student learning motivation. The method used in this research is the literature review method, the data collection used is by examining various case studies that are relevant to the research. Until later, from the results of data collection, it can be concluded that in increasing student learning motivation, teachers must master several teaching skills and one of them is skills in mastering learning variations.